2008
DOI: 10.1088/0022-3727/41/6/065402
|View full text |Cite
|
Sign up to set email alerts
|

Structure of CdZnTe films on glass

Abstract: Polycrystalline Cd1−xZnxTe films were grown on glass substrates over the full range of compositions (0 < x < 1) by metal–organic chemical vapour deposition at 480 °C. The films (∼5 µm thick) showed uniform texture oriented along the ⟨1 1 1⟩ direction, perpendicular to the substrate, independent of the film composition. The dependence of the lattice parameter of cubic Cd1−xZnxTe on the composition followed Vegard's law. The thick Cd1−xZnxTe films were shown to be of a single phase and structurally stable. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 37 publications
5
30
0
Order By: Relevance
“…At present different methods of Cd 1 À x Zn x Te films deposition such as metalorganic vapor-phase epitaxy [9] metal-organic chemical vapor deposition [10], pulsed laser deposition [11], thermal Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/jlumin evaporation [12,13], brush plating technique [14], magnetron sputtering [15], hot wall epitaxy [16], laser ablation [11] were used. Earlier [17], it was shown that a low cost close-spaced vacuum sublimation (CSVS) method makes it possible to deposit the stoichiometric films of II-VI semiconductors with the controllable physical properties using a glass as substrate.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…At present different methods of Cd 1 À x Zn x Te films deposition such as metalorganic vapor-phase epitaxy [9] metal-organic chemical vapor deposition [10], pulsed laser deposition [11], thermal Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/jlumin evaporation [12,13], brush plating technique [14], magnetron sputtering [15], hot wall epitaxy [16], laser ablation [11] were used. Earlier [17], it was shown that a low cost close-spaced vacuum sublimation (CSVS) method makes it possible to deposit the stoichiometric films of II-VI semiconductors with the controllable physical properties using a glass as substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, different properties of thin and thick films have been studied in Refs. [10,[26][27][28]. It was shown [26] that Cd 1 À x Zn x Te (xr 0.54) layers with typical thicknesses of 2-3 μm deposited by molecular beam epitaxy on GaAs substrates observe narrow (PL) bands at higher energies which are attributed to bound exciton (BE) recombinations and the broader bands e-A, which arising from band-to-acceptor radiative transitions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations